The great rush - Károly Fazekas (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
This paper provides a summary of the latest advancements in generative artificial intelligence using large language models over the past six months. The impact of this breakthrough remains uncertain, but it is evident that GPT is a General-Purpose Technology (GPT) that will significantly alter various aspects of our economy and society in ways that are yet to be fully comprehended. While it is essential for the government to regulate GPT technology, it is inevitable that the technology will continue to expand and evolve at a rapid pace. There is no doubt that every corner of the new world if it exists at all, will be covered by millions of forms of artificial intelligence. The taming of AIs and successful social and personal cooperation with domesticated AIs could ensure our survival and prosperity in that world. Whether or not AIs are capable and willing to cooperate will populate the new world is neither an individual nor a national matter. But how a country and its people fare in the new world is more so.
Keywords: O31; O33; Q55; 330; innovation and invention: processes and incentives; technological change: choices and consequences; diffusion processes; technological innovation